P-110 Survival of patients following discharge from a hospice. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Baker, Laura; Tredgett, Kate
Abstract : Background: Hospice beds are a finite resource increasingly unable to support long-term admissions without specialist needs. However, it has been suggested that moving a patient may hasten death via "relocation syndrome." Moves should be avoided where prognosis is less than 4 weeks. Methods: A retrospective observational study was carried out in a hospice. Computer-based records were analysed to calculate survival post-discharge over a three month period. Patient demographics, the length and purpose of admission, and preferred place of death (PPD) were recorded. Results: 63 patients were included. 44 died in the hospice and 19 were discharged. Of those who were discharged, 16% (n = 10) went home and 14% (n = 9) went to a care home. The median survival of those discharged home was 61.5 days compared to 12 days for those discharged to a care home. The PPD was met more often in those who died in the hospice. Those discharged to care homes were the most elderly; median age care home = 79, home = 72, hospice = 74.5 and had the longest admissions prior to transfer; median admission for care home discharge = 29 days, home = 13 days, hospice death = 9 days. Discussion: Prognostication is notoriously difficult. However, with the aim of a "good death, " it would have been preferable to avoid the discharges following which survival was short. The more rapid decline observed in those discharged to care homes may be anticipatable. Such individuals are likely frailer and more dependent. However, as patients who are thought to be unstable are not discharged, it is possible that this was influenced by 'relocation syndrome'. Prolonged hospice admissions for patients discharged to care homes may signify particularly complex needs. In the current climate of difficulty accessing funding for care and placements, it may reflect a prolonged discharge planning process during which the window of opportunity for successful placement is lost. Further research is needed to explore this.